Mastication of polyolefins alters the microbial composition in Galleria mellonella. (1st July 2021) - Peydaei, Asal; Bagheri, Hedayat; Gurevich, Leonid; de Jonge, Nadieh; Nielsen, Jeppe Lund
Abstract: Recent studies have indicated that Galleria mellonella larvae ingest polyethylene films and the degradation mechanism could inspire biotechnological exploitation for degrading plastic to eliminate global pollution from plastic waste. In this study, we tested the chemical compositions of masticated and ingested different plastic types by G. mellonella . High throughput sequencing of 16S rRNA gene was used to characterize the alteration of the microbial communities derived from salivary glands, gut contents and whole G. mellonella larvae. Our results indicated that G. mellonella is able to masticate polyethylene (PE), expanded polystyrene (EPS) and polypropylene (PP) and convert it to small particles with very large and chemically modified surfaces. The characteristics of the polymer affect the rate of damage. Formation of functional carbonyl groups on the appearance of oxidized metabolic intermediates of polyolefins in the frass samples observed. We found that the mastication of EPS, PP or PE could significantly alter the microbial composition in the gut content while it did not appear to influence the salivary glands microbial community. Representatives of Desulfovibrio vulgaris and Enterobacter grew with the PE diet while mastication of polystyrene and polypropylene increased the abundance of Enterococcus. The evaluation of bacterial communities in whole larvae confirmed the obtained result and additionally showed that the abundance of Paenibacillus, Corynebacterium and Commamonadaceae increased by Styrofoam (EPS) consumption. Graphical abstract: Image 1 Highlights: Chemical modifications of the polyethylene, polystyrene and polypropylene after exposure to G. mellonella . mastication of EPS, PP or PE could significantly alter the microbial composition in gut content. Polyolefin mastication did not influence the salivary glands microbial community. Representatives of Desulfovibrio vulgaris and Enterobacter were significantly enriched with the PE diets. mastication of polystyrene and polypropylene increased the abundance of Enterococcus in the gut content.